2009
DOI: 10.1186/1477-7819-7-73
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium septicum sepsis and colorectal cancer - a reminder

Abstract: Background: Spontaneous clostridium septicum infections are rare and are associated with a high mortality. Association of clostridium infection with colorectal malignancies have been previously reported and most cases are described in tumours of the ascending colon. We report our experience of clostridium septicum infection in the presence of tumour perforation in a series of two patients as a reminder of its association with sepsis in the presence of colorectal malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 16 publications
0
57
0
3
Order By: Relevance
“…Interestingly, blood sample was obtained before colonoscopy and it is suggested that these microorganisms were able to achieve bloodstream through tumor tissue and they may remain in state of bacteremia for long period [6]. In this case, the infection in rectal cancer involves disruption of the normal barrier due to tumor-induced ulceration, followed by bloodstream invasion, in accordance with Mirza [7] Bacteremia caused by anaerobic bacteria represents from 0.5% to 12% of the total of bacteremia, and the mortality is approximately between 25% and 44% [8]. Studies have shown that bacterial community in an individual is relatively stable along the distal digestive tract [9].…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, blood sample was obtained before colonoscopy and it is suggested that these microorganisms were able to achieve bloodstream through tumor tissue and they may remain in state of bacteremia for long period [6]. In this case, the infection in rectal cancer involves disruption of the normal barrier due to tumor-induced ulceration, followed by bloodstream invasion, in accordance with Mirza [7] Bacteremia caused by anaerobic bacteria represents from 0.5% to 12% of the total of bacteremia, and the mortality is approximately between 25% and 44% [8]. Studies have shown that bacterial community in an individual is relatively stable along the distal digestive tract [9].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, recurrent infections may occur in both CRC and aplastic anemia. Streptoccocusbovis septicemia is classically associated with colorectal cancer [11] ; other organisms include Enterobacter [12] and Clostridium species [13] . Infections that are seen in aplastic anemia also include Streptoccocus and Clostridium species, in addition to Escherichia coli and others [14] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to S. gallolyticus endocarditis, also Clostridium septicum infections have been clinically associated with sporadic CRC (Chew & Lubowski, 2001;Mirza et al, 2009). C. septicum is not considered to be part of the normal intestinal microbiota and is a rare cause of bacteremia (<1% of all cases).…”
Section: Clostridium Septicummentioning
confidence: 99%